Study Of A Knowledge Management Application In A Franchising Learning Business - Lim , Teck Ting (2009)
This research project aimed to understand the influence of knowledge management processes on the overall business performance of an interlinked, franchised educational organization in Malaysia. A PM framework was used to develop the business process oriented knowledge road map for enhancing the knowledge transfer.